A COMPARATIVE STUDY OF THE APPLICATION OF DIFFERENT TCD IN CRANKSHAFT FATIGUE PROPERTY PREDICTION - SUN SongSong; WAN MaoSong; XU XiaoMei (Jixie qiangdu)
This paper,focus on the crankshaft bending fatigue property prediction research,first analyzes the stress distribution fitting approach based on a stress gradient approach,then the fatigue property of the crankshaft with the same material but different structure is predicted,finally corresponding experiment verification is conducted. The results show that for the modified indirect defined theory of critical distance（ ITCD）,the predictions based on both the line method and point method are almost unanimity and may contain some errors. While for the direct defined theory of critical distance（ DTCD）,the critical line approach has a much better accuracy than the critical point approach,so this approach is much more suitable to be taken into the actual engineering application.